(untitled) (Research, Society and Development, 2022)
The present article aimed to conduct a literature review to analyze publications on school management in the context of inclusive education, using the search terms: "school management" and "inclusion" and "disability" and "micropolitics" and "subjectivity production", in the search portal Google Academic. The results showed a total of 3350 publications, with a cut from the year 2017 1330 publications were found, of these only articles were selected, since part of the results referred to master’s dissertations and doctoral theses, as well as e-books, among other links. Of this total, only 09 articles dealt with the theme of subjectivity production. In the analyses, we found approaches about the importance of care, of welcoming, about the excessive referral of students by the school due to the abnormality that considers the students with deviation from the standard. We observed that researchers who set out to investigate this theme took a political stand against the atrocities to life that this performance society has imprisoned us, leading us to see and recognize otherness as a singular expression of life.